2008
DOI: 10.1073/pnas.0804336105
|View full text |Cite
|
Sign up to set email alerts
|

A modified cysteinyl-labeling assay reveals reversible oxidation of protein tyrosine phosphatases in angiomyolipoma cells

Abstract: The production of reactive oxygen species (ROS) exerts an additional tier of control over tyrosine phosphorylation-dependent signal transduction by transiently inhibiting the catalytic activity of specific protein tyrosine phosphatases (PTPs). Hence, the ability to detect reversible oxidation of PTPs in vivo is critical to understanding the complex biological role of ROS in the control of cellular signaling. Here, we describe an assay for identifying those PTPs that are reversibly oxidized in vivo, which utili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
90
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(94 citation statements)
references
References 29 publications
4
90
0
Order By: Relevance
“…The role of ROS-dependent redox dysregulation in tumor progression has been studied recently in much detail in human melanoma where overexpression of Akt converts radial (noninvasive) to vertical (invasive) growth phase tumors with increased generation of superoxide originating from NOX4 upregulation, preferential glycolytic energy metabolism, and VEGFdependent angiogenesis (115,134). In this context, it should also be mentioned that the antagonist of phosphoinositidedependent Akt activation and tumor suppressor PTEN and other members of the protein tyrosine phosphatase superfamily are established molecular targets of ROS signaling, chemically inactivated by ROS-dependent oxidation of essential cysteine residues facilitating tumorigenic tyrosine kinase receptor signaling (36,214,215,247,387).…”
Section: Redox Dysregulation As Anticancer Drug Targetmentioning
confidence: 99%
“…The role of ROS-dependent redox dysregulation in tumor progression has been studied recently in much detail in human melanoma where overexpression of Akt converts radial (noninvasive) to vertical (invasive) growth phase tumors with increased generation of superoxide originating from NOX4 upregulation, preferential glycolytic energy metabolism, and VEGFdependent angiogenesis (115,134). In this context, it should also be mentioned that the antagonist of phosphoinositidedependent Akt activation and tumor suppressor PTEN and other members of the protein tyrosine phosphatase superfamily are established molecular targets of ROS signaling, chemically inactivated by ROS-dependent oxidation of essential cysteine residues facilitating tumorigenic tyrosine kinase receptor signaling (36,214,215,247,387).…”
Section: Redox Dysregulation As Anticancer Drug Targetmentioning
confidence: 99%
“…Consequently, alterations in expression levels or the specific activity of PTPs will affect the cellular response to ligands of RTKs. With regard to the PDGF β-receptor, a series of PTPs, including T cell protein tyrosine phosphatase (TC-PTP), density enhanced phosphatase-1 (DEP-1), SHP-2, and PTP-1B, have been found to modulate receptor signaling (4)(5)(6)(7). Detailed analyses of the consequences of deletion of individual PTPs have shown that individual PDGF receptorantagonizing PTPs preferentially dephosphorylate particular phospho-tyrosine residues of the receptor and thereby are able to modulate the signaling output (4,(8)(9)(10).…”
mentioning
confidence: 99%
“…24,25 Our studies suggest that the pathogenesis of vascular malformations may result from aberrant dusp-5 and snrk-1 signaling. Reactive oxygen species has been reported to inhibit the catalytic activity of specific tyrosine phosphatases (dusp-1) in an angiomyolipoma cell model 26 and treatment using nicotinamide adenine dinucleotide phosphate (reduced form) oxidase (Nox) inhibitors abolished hemangioma growth in vivo via blockage of angiopoietin-2 production. 27 It makes sense that mutations in dusp-5 and snrk-1 play an integral role in these conditions because both genes work together to maintain vascular precursors.…”
Section: Discussionmentioning
confidence: 99%